Baseline updating method for structural damage identification using modal residual force and grey wolf optimization. Issue 4 (2nd April 2020) - Zare Hosseinzadeh, Ali; Ghodrati Amiri, Gholamreza; Jafarian Abyaneh, Mojtaba; Seyed Razzaghi, Seyed Ali; Ghadimi Hamzehkolaei, Azadeh
ABSTRACT: This article presents two effective optimization-based model-updating approaches for structural damage identification using the modal residual force (MRF) concept. The first objective function employs a direct data-fitting procedure to inspect the amount of approaching between entries of the calculated MRF vectors for the monitored and analytical models of the structure. The second objective function uses the modal assurance criterion as a geometric tracing criterion to evaluate the amount of accordance between two vectors. The proposed objective functions are solved with a novel metaheuristic optimization technique, the grey wolf optimization algorithm. Four numerical examples are studied to demonstrate the efficiency of the proposed methods. Moreover, studies are conducted not only to assess the robustness of the methods in more realistic circumstances, but also to justify the necessity of using these techniques. Based on the obtained results, the second objective function is more sensitive to structural damage than the first objective function.